2021
DOI: 10.3390/children8121139
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Weight of Spinal Pain in Children and Adolescents

Abstract: Spinal pain in adults is a significant burden, from an individual and societal perspective. According to epidemiologic data, spinal pain is commonly found in children and adolescents, where evidence emerging over the past decade has demonstrated that spinal pain in adults can, in many cases, be traced back to childhood or adolescence. Nevertheless, very little focus has been on how to best manage spinal pain in younger age groups. The purpose of this article is to put the focus on spinal pain in children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
2
1
Order By: Relevance
“…which was not in accordance with previous findings (Hoskins et al, 2009;Koyama et al, 2022;Morimoto et al, 2022) (Trompeter et al, 2017). India has A cross-sectional study of 1,532 young individuals aged 18 to 35 years discovered that the prevalence of LBP was 42.4% per year and 22.8% every week (Palsson et al, 2021). Another study carried out among 206 individuals reported that (64.6%) of the patients had LBP for around 1 year followed by 11.2% of the patients who had it for 1 month or more and only 9.2% of them were suffering for over 3 years (Ramdas & Jella, 2018).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…which was not in accordance with previous findings (Hoskins et al, 2009;Koyama et al, 2022;Morimoto et al, 2022) (Trompeter et al, 2017). India has A cross-sectional study of 1,532 young individuals aged 18 to 35 years discovered that the prevalence of LBP was 42.4% per year and 22.8% every week (Palsson et al, 2021). Another study carried out among 206 individuals reported that (64.6%) of the patients had LBP for around 1 year followed by 11.2% of the patients who had it for 1 month or more and only 9.2% of them were suffering for over 3 years (Ramdas & Jella, 2018).…”
Section: Resultscontrasting
confidence: 72%
“…Another study done in India found that marital status, previous history of spinal issues, vigorous exercise, work satisfaction, monotony, stress, daily amount of study hours, and family history of spine problems were all substantially linked with LBP (p0.05). Age, gender, smoking, drunkenness, coffee consumption, mode and duration of travel, nutrition, frequency of weightlifting, wearing heels, studying posture, and frequency and kind of sports activities, on the other hand, were not related to LBP (Palsson et al, 2021). Previous research has shown that having a high body mass index (BMI) is connected with a higher risk of LBP (Franchini et al, 2022).…”
Section: Resultsmentioning
confidence: 97%
“…School bag weight, chair design, muscle strength, hypermobility, posture, and alignment are all factors which, at some points, were thought to influence the development of LBP in adolescence. However, there is a general lack of evidence to support that any of these factors should be considered as a risk factor for adolescent LBP (61)(62)(63)(64).…”
Section: Risk Factors For Low Back Pain In Adolescentsmentioning
confidence: 99%